Relationship between academic procrastination and self-esteem among dental students in Bengaluru City - Priya Babu; K Mahesh Chandra; M K Vanishree; N Amritha (Wolters Kluwer Medknow Publications, 2019)
Background: Procrastination may be conceptualized as a behavioral self-handicap. In education and training, the term academic procrastination is commonly used to denote the delay in academic activities. A person who procrastinates starts feeling powerless and hopeless; his confidence suffers and future seems dark and can lead to low self-esteem. Aim: The aim of this study was to assess the relationship between academic procrastination and self-esteem among dental students in Bengaluru City, Karnataka, India. Material and Methods: The current cross-sectional study was conducted among dental students from three different dental institutions in Bengaluru. The sample consisted of 255 dental students. Data were collected through questionnaire using the Tuckman Academic Procrastination Scale and Rosenberg Self-Esteem Scale. The data collected were analyzed using SPSS software version 14.0. Independent Student's t-test, ANOVA, and Pearson's correlation test were performed. P < 0.05 was considered statistically significant. Results: The results indicated that a significant weak positive correlation (r = 0.25, P < 0.001) existed between academic procrastination scores and self-esteem scores. There was a significant difference in the mean score of academic procrastination between males (40.81 ± 6.87) and females (42.80 ± 7.25) (P = 0.03). Conclusions: The current study found out that students with high self-esteem procrastinate less, whereas those who procrastinate more have comparatively lower self-esteem. Timely intervention can help students improve their skills such as time management and study habits.